Assessing the inactivation efficiency of Ar/O2 plasma treatment against Listeria monocytogenes cells: Sublethal injury and inactivation kinetics. (August 2019) - Pan, Yuanyuan; Cheng, Jun-Hu; Lv, Xiaoye; Sun, Da-Wen
Abstract: A study was carried out to detect and assess possible sublethal injury and inactivation kinetics of Listeria monocytogenes suspended in phosphate-buffered saline (0.01 M PBS, pH = 7.4) by Ar/O2 plasma treatment. Results showed that both the germicidal effect and proportion of sublethally injured cells exhibited a time-dependent behavior, and post-treatment storage further extended the plasma lethality. The cytoplasmic enzymatic activity was reduced, but no considerable leakage levels of intracellular DNA and protein occurred. Incorporating the post-treatment storage for 48 h substantially decreased the intensity of intracellular reactive oxygen species (ROS) ( p  < 0.01) to relatively low level with no chemical residues. Moreover, the inactivation kinetics was well described by Weibull model (RMSENS  = 0.074, RMSES  = 0.093). The current study provided valuable information on the inactivation kinetics of L. monocytogenes and demonstrated the potential applications of plasma-mediated sterilization in liquid foodstuffs. Highlights: Germicidal effect exhibited time-dependent behaviors. Treatment for 8 min increased the proportion of sublethally injured cells by 45.8%. Storage for 48 h substantially decreased level of intracellular reactive species. L. monocytogenes was mainly inactivated by intracellular damage. The inactivation kinetics was well described by Weibull model.